Development of Computer Network Security Management at North Tabukan 1 State Vocational School - Mananggel, Arther Valentino; Olii, Djami; Parinsi, Mario Tulenan; Rompas, Parabelem Tinno Dolf (International Journal of Information Technology and Education, 2023)
The development of the internet at this time makes all companies, especially SMKN 1 Tabukan Utara, able to utilize internet technology in supporting computer-based information systems. For this place to run its business properly, it must be supported by an information system and supported by a good computer network infrastructure. Computer network infrastructure in the SMKN 1 Tabukan Utara still has several disadvantages such as the absence of website blocking, login authentication, and regular bandwidth distribution. To overcome these problems, it is necessary to design the network properly, as for the methods used in designing this network using the Network Development Life Cycle (NDLC). This method can develop existing competition through several stages of the process, namely analysis, design, prototype simulation, implementation, monitoring, and management. The results of this study are in the form of a home computer network SMKN 1 Tabukan Utara that implements Captive Portal, Virtual Lan, Firewall Filtering, L7 protocol, and Bandwidth Management.